Biological Systematics : Principles and Applications - Schuh, Randall T. (Book collections on Project MUSE., 2009)
Biological Systematics: Principles and Applications draws equally from examples in botany and zoology to provide a modern account of cladistic principles and techniques. It is a core systematics textbook with a focus on parsimony-based approaches for students and biologists interested in systematics and comparative biology. Randall T. Schuh and Andrew V.Z. Brower cover: -the history and philosophy of systematics and nomenclature;-the mechanics and methods of analysis and evaluation of results;-the practical applications of results and wider relevance within biological classification, biogeography, adaptation and coevolution, biodiversity, and conservation; and-software applications. This new and thoroughly revised edition reflects the exponential growth in the use of DNA sequence data in systematics. New data techniques and a notable increase in the number of examples from molecular systematics will be of interest to students increasingly involved in molecular and genetic work.